Student Charges, Student Financial Aid, and Access to Postsecondary Education A Report to the Governor and the Legislature in Response to Assembly Concurrent Resolution 81 [and Responses to the Commission's Report]. - California State Postsecondary Education Commission, Sacramento; California State Postsecondary Education Commission, Sacramento ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
In response to legislative mandate, this report assesses the impact of student charges on access to public postsecondary education and provides policy recommendations. Part I of the report summarizes the state's goals for postsecondary education, reviews past policies for achieving these goals, and outlines future options in a time of financial constraint. Part II presents six recommendations and the principles upon which they are based for maintaining access, high quality, and equitable student charges through explicitly defined state policies and shared individual and public support for postsecondary education. Part III offers four recommendations in response to the legislature's concerns about the distribution of financial aid to students, the use of revenues from student charges, and the impact of student charges on the roles and missions of the segments of the postsecondary system within the state's master plan. Part IV provides a brief conclusion pointing out the strengths and limitations of the recommendations. Appendices include a list of discussion papers provided by the California Postsecondary Education Commission's advisory committee, resource documents, and data on appropriations and enrollments in California postsecondary education for 1979-80 to 1981-82. Responses to the report by members of the Commission's advisory committee are included as requested by the California legislature. (Author/HB)
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; College Role; Community Colleges; Educational Policy; Educational Quality; Postsecondary Education; State Colleges; Statewide Planning; Student Costs; Student Financial Aid; Tuition; California; Opinion Papers